Gender differences in relationship preferences after union dissolution. (December 2015) - Poortman, Anne-Rigt; Hewitt, Belinda
Abstract: Women less often remarry or cohabit again after union dissolution than men. To develop our understanding of this gender gap, we look at men's and women's relationship preferences following the dissolution of marital and cohabiting unions. Using the Dutch Generations and Gender Survey Study ( N  = 973), results show that divorced or separated women less often want to live with a partner again than men, and this holds for both singles and persons with a steady partner. Men and women generally do not differ in their desire to marry, except when they cohabit. Cohabiting women express a weaker desire for marriage than cohabiting men. Overall, we find women are less willing than men to proceed to the next step in a relationship—from dating, to living together, to marriage. Children from previous relationships are pivotal for both men's and women's relationship preferences. Having (young) resident prior children attenuates women's desire to live together, whereas for men it is the frequency of contact with non-resident prior children that matters. Because women more often than men have primary care of children after divorce or separation, the gender difference in the desire to live with another partner is largely explained by women's greater involvement with children from previous relationships. We conclude that understanding preferences can provide better insight into gendered differences in relationship formation after union dissolution.